Platelet Ceria Catalysts from Solution Combustion and Effect of Iron Doping for Synthesis of Dimethyl Carbonate from CO2 - Nicoletta Rusta; Valentina Mameli; Pier Carlo Ricci; Stefania Porcu; Panpailin Seeharaj; Aryane Marciniak; Evelyn Santos; Odivaldo Cambraia Alves; Claudio Mota; Elisabetta Rombi; Carla Cannas (My University, 2024)
Solution combustion (SC) remains among the most promising synthetic strategies for the production of crystalline nanopowders from an aqueous medium, due to its easiness, time and cost‐effectiveness, scalability and eco‐friendliness. In this work, this method was selected to obtain anisometric ceria‐based nanoparticles applied as catalysts for the direct synthesis of dimethyl carbonate. The catalytic performances were studied for the ceria and Fe‐doped ceria from SC (CeO2‐SC, Ce0.9Fe0.1O2‐SC) in comparison with the ceria nanorods (CeO2‐HT, Ce0.9Fe0.1O2‐HT) obtained by hydrothermal (HT) method, one of the most studied systems in the literature. Indeed, the ceria nanoparticles obtained by SC were found to be highly crystalline, platelet‐shaped, arranged in a mosaic‐like assembly and with smaller crystallite size (≈6 nm vs. ≈17 nm) and higher surface area (80 m2 g‐1vs. 26 m2 g‐1) for the undoped sample with respect to the Fe‐doped counterpart. Although all samples exhibit an anisometric morphology that should favor the exposition of specific crystalline planes, HT‐samples showed better performances due to higher oxygen vacancies concentration and lower amount of strong basic and acid sites.
Keywords: Nanorod; Hydrothermal Synthesis; Dimethyl carbonate; Catalytic Processes in Materials Science